Quality of Chicken Patties with Different Levels of Tapioca Flour Prepared by Using Food Processer - Reddy, B. Ramachendra; Mandal, P.K.; Kasthuri , S.; Pal , U.K. (Journal of Meat Science, 2019)
A study was conducted to prepare spent hen meat patties by incorporation of tapioca flour and to compare the quality and economics  of such patties processed by using food processor and bowl chopper. Chicken meat patties with 3% maida (control) and different levels  of tapioca flour (3, 5 and 7%) prepared by using food processor were subjected to physico-chemical, chemical composition and sensory  analysis. Results revealed that patties containing 5 and 7% tapioca flour had significantly (P0.05) differences were observed in sensory quality of patties containing different levels of tapioca flour, but 5% tapioca flour incorporated patties  had non-significantly higher overall acceptability. The patties prepared with incorporation of 3 and 5% tapioca flour had significantly  (P
Keywords: Spent hen meat patties; Tapioca flour; Food processor; Bowl chopper; Physico-chemical quality; Sensory quality